TEACHING TRAINING PRACTICE CHALLENGES FACED BY ENGLISH DEPARTMENT STUDENTS DURING PANDEMIC COVID-19 TIME - Herlina Sambi (Teaching English as a Foreign Language Overseas Journal, 2022)
This research focuses on the challenges faced students in doing teaching training practice. The objective of this study was to find out the challenges faced by the English Department students in doing teaching training practiceat school during the pandemic covid 19 time. This research used descriptive qualitative method. The population of this study is English students of UKI Toraja. The population was selected by using snowball sampling technique. To collect data the writer used interviews .Then the data is analyzed using four main phases, namely collection,reduction, data display, and conclusion.Based on the results of research through interviews, the researcher found that there were some challenges faced by English depertment students of UKI Toraja in doing teaching training practice at school during pandemic covid-19 time. They are learning of short time, Inability to manage students’ behavior, lack of routine in the classroom, difficulty in encourage critical thinking on the students, difficulty inplementing approaches and strategies in learning, none extra and intervetion activities, difficulty in present instructional materials. In summary there were seven challenges faced by English department students of UKI Toraja in doing teaching training